Complejidad argumentativa individual escrita en estudiantes universitarios ingresantes y avanzados - Tuzinkievicz, María Agustina (2018)
The investigation compares argumentative individual complexity written in socio-scientific tasks of university students of Psychology, depending on years of study and the presence/absence of an additional representation system (graphs) of information external. 72 students from the argentine university participated. They gave their opinion about a socio-scientific situation that included arguments for and against it, and a group received additional graphic information. The productions were coded according to: (a) whether it was an argumentative text; (b) the relation to the argumentative texts, the number of arguments, the type of difference of opinion, the argumentative structure, and confirmatory bias; (c) he use of information. The results show a relationship between first-year students and non-argumentative texts and between advanced students and the use of argumentative texts. Both types of students reduced the number of arguments when there was no additional information. The results are discussed in relation to both  theoretical conceptualization of argumentative competence and the design of educative materials to university.